2016
DOI: 10.1103/physrevphyseducres.12.020119
|View full text |Cite
|
Sign up to set email alerts
|

Gender discrimination in physics and astronomy: Graduate student experiences of sexism and gender microaggressions

Abstract: This paper is part of the Focused Collection on Gender in Physics.] Sexism occurs when men are believed to be superior to women, and is thought to be one of the reasons for women's underrepresentation in physics and astronomy. The issue of sexism in physics and astronomy has not been thoroughly explored in the physics education literature and there is currently no clear language for discussing sexism in the field. This article seeks to begin a conversation on sexism in physics and astronomy and offer a startin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
96
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(105 citation statements)
references
References 41 publications
3
96
0
6
Order By: Relevance
“…Evidence 5 provided 4 StarLab is a pseudonym for the research group that both Molly and Ruby were members of at Eastern University. 5 As there are several sources for data in each case study (interviews, photo-journals, field notes), I have indicated the source code for each piece of data (INT ¼ interview, PJ ¼ photo-journal, FN ¼ fieldnotes), along with cataloguing codes. Transcriptions are presented verbatim with syntax errors indicated as [sic], and pauses in the transcript as ellipses […].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Evidence 5 provided 4 StarLab is a pseudonym for the research group that both Molly and Ruby were members of at Eastern University. 5 As there are several sources for data in each case study (interviews, photo-journals, field notes), I have indicated the source code for each piece of data (INT ¼ interview, PJ ¼ photo-journal, FN ¼ fieldnotes), along with cataloguing codes. Transcriptions are presented verbatim with syntax errors indicated as [sic], and pauses in the transcript as ellipses […].…”
Section: Resultsmentioning
confidence: 99%
“…This perspective permits the examination of a more fluid range of gender identities, and how these intersect with a range of astrophysicist identities. The analysis is also shifted from identifying structural factors (e.g., mentoring [5] or departmental support [22]) related to women's persistence in the field, to the subtle ways that gender can influence students' beliefs about who they must be to engage in astrophysics culture.…”
Section: A Identity Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, it is increasingly recognized that physics education is not simply about the transfer of a body of knowledge but also about engaging people and developing their capacities in (and in the long run helping define) the discourse, practices, and community norms of physics (Refs. [37][38][39][40][41]). …”
Section: A Sociocultural Perspectivesmentioning
confidence: 99%